Cerebral abscess as a complication of a dental abscess - Regeer, Jeroen; Groote, Bert De; Damme, Emmi van (International Journal of Contemporary Pediatrics, 2019)
A dental abscess, most often caused by inadequate oral hygiene, can be easily treated if timely diagnosed. However, delay in treatment can lead to bacterial dissemination and serious complications, such as development of a cerebral abscess. Authors retrospectively analyzed a case of a 15-year-old boy admitted to our pediatrics department with a cerebral abscess due to a dental abscess. A 15-year-old patient presented with supra-orbital swelling which due to previous delay in dental treatment had caused dental, orbital and cerebral abscess formation. After extraction of the affected tooth and six weeks of IV antibiotics the size of the cerebral abscess was practically unchanged. An epidural drainage and further treatment with IV antibiotics were needed to eliminate the cerebral abscess. The urgency of dental treatment to inhibit further microbial spread is of great importance and delay can have serious consequences.